Uncommon presentations of common variable immunodeficiency. Issue 12 (2nd December 2022) - Alok, Akankcha; Aslam, Sadaf; Greene, John N
Abstract : Common variable immunodeficiency (CVID) is a primary immunodeficiency disorder that causes decreased immunity and increased susceptibility to infections. It affects B lymphocyte differentiation, resulting in predominantly bacterial and less frequently viral, fungal, and protozoal infections. The respiratory and gastrointestinal tracts where antibody defences are essential are usually affected. Individuals with CVID are also predisposed to developing lymphoid and gastrointestinal malignancies. We present two cases with rare infectious and oncological complications of CVID, including a patient with Mycobacterium avium comple x-intracellular infection and ovarian cancer, and another patient with group B Streptococcus empyema of the lung with acute myeloid leukaemia. The main objective of this study is to highlight how CVID-induced hypogammaglobulinaemia can lead to rare infections and malignancies. The management of these complications can vary according to severity, but an awareness of their existence is crucial to diagnose them promptly in an already immunocompromised CVID patient.